2021
DOI: 10.1371/journal.pone.0260969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on bike-sharing demand and hire time: Evidence from Santander Cycles in London

Abstract: The COVID-19 pandemic has been influencing travel behaviour in many urban areas around the world since the beginning of 2020. As a consequence, bike-sharing schemes have been affected—partly due to the change in travel demand and behaviour as well as a shift from public transit. This study estimates the varying effect of the COVID-19 pandemic on the London bike-sharing system (Santander Cycles) over the period March–December 2020. We employed a Bayesian second-order random walk time-series model to account for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…However, there are several cases in which despite an initial increase in using BS systems during the first months of the pandemic, ridership declined for several months in 2020 [48][49][50][51][52][53]. There are also systems recovering from the effects of the pandemic and mainly lockdown measures applied in many countries; for example, in the UK, the latest data show a significant recovery [54]. A study estimating the effect of the pandemic on the London BS system over the period March-December 2020 indicated that although a reduction in cycle hires was recorded in March and April 2020, the demand increased after May 2020 and even more during April, May, and June 2020 the bikes were hired for longer trips (perhaps as the authors mention due to a shift from public transit) [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several cases in which despite an initial increase in using BS systems during the first months of the pandemic, ridership declined for several months in 2020 [48][49][50][51][52][53]. There are also systems recovering from the effects of the pandemic and mainly lockdown measures applied in many countries; for example, in the UK, the latest data show a significant recovery [54]. A study estimating the effect of the pandemic on the London BS system over the period March-December 2020 indicated that although a reduction in cycle hires was recorded in March and April 2020, the demand increased after May 2020 and even more during April, May, and June 2020 the bikes were hired for longer trips (perhaps as the authors mention due to a shift from public transit) [54].…”
Section: Discussionmentioning
confidence: 99%
“…There are also systems recovering from the effects of the pandemic and mainly lockdown measures applied in many countries; for example, in the UK, the latest data show a significant recovery [54]. A study estimating the effect of the pandemic on the London BS system over the period March-December 2020 indicated that although a reduction in cycle hires was recorded in March and April 2020, the demand increased after May 2020 and even more during April, May, and June 2020 the bikes were hired for longer trips (perhaps as the authors mention due to a shift from public transit) [54]. It is clear that people have reacted differently worldwide concerning the usage of BS systems during the pandemic, making each case unique.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors found evidence that a modal shift from public transport to bike-sharing occurred and therefore consider the bike-sharing system is a more resilient option than the subway system. Similarly, Heydari et al (2021) view the bike-sharing system in London as a resilient part of the urban transportation system as shared bicycle usage did not decrease significantly. However, the authors show that usage times increased during lockdown periods, indicating changes in people's mobility behavior and the usage of bike-sharing systems as a substitution for public transport.…”
Section: General Mobility and Cycling Trends During The Covid-19 Pand...mentioning
confidence: 98%
“…The third one is centered on user behaviors via survey analysis. [HKB21] provides an interesting summary of the diversity of published results.…”
Section: Introductionmentioning
confidence: 99%
“…Let us focus on some relevant recent papers falling within the first type of approach. With a Bayesian time-series model on monthly aggregated data, [HKB21] estimates the impact of the pandemic on both trip duration and number of trips in London. Confirming previous results, in (e.g., [LZZR21,WN21]), the authors observe that trips are longer than expected during and after the spring 2020 lockdown.…”
Section: Introductionmentioning
confidence: 99%